NEW PARADIGM ON SINLAMMIM KAFAH IN ISLAMIC ECONOMICS - Roikhan Moch Aziz (Signifikan: Jurnal Ilmu Ekonomi, 2012)
The result of this new finding is Kaffah approach in Islamic Economics. The ontology of Kaffah concept is Islam. This conjunction with existing life system in human being, environment, and universe. All creations by God could be pointed as the form of Islam. Islam can be meant as a system with holistic approach, comprehensive view, and Kaffah perspective. Then Islam as a system becomes the root of concept to integrate in economic concept and the epistemology is Kaffah. Then axiology relation has 2 matter representing good and bad. Sinlammim as a methodology can be approached by digital root tool.DOI: 10.15408/sjie.v1i2.2604